Investigating the level of Safety Considerations in Radiology Centers (North of Iran): Cross –Sectional Study - Vajiheh, Keshavarz; Seyed, Ali Rahimi (International Journal of Occupational and Environmental Medicine, 2021)
Background and Purpose Providing health care is the basic right of people(1). Diagnostic radiology is one of the main procedures in health care services and proper benefiting from this technology is brought only under well planning and management(1). Supervision of the available condition and its comparison with the recommended standards is a key role in assessing assurance from the benefit of these instruments (2). Data show that more than 80% of patients referring to these hospitals need radiology image (3).Improper service causes repetition of radiography and even wrong diagnosis, as a results threatening health of the patients (3) lack of protective barrier leads to the exposure of the staff to X-ray which is obviously carcinogen us (4). It happens that the instruments are not working properly, like of symmetry in X-ray field, defects in collimators, lack of adjusting ray field and X-ray, low quality or defective developing machine, lack of proper protective barrier, using low quality film and drugs, lack of protective barrier for children, all of which cause severe hazards for the patients and staff (4). Materials and Methods The crucial aim of medical services is to provide the public with their needs which are very important. The sensitivity of such services is to such an extent that in case of lack of care, the hazards are too high. In evaluation of health services, the first thing is to evaluate the device used. Methods, efficiency, profits and their combination for prevention and eradication of diseases are also important. Therefore to gain this goal, it is necessary the obtain results comparable with recommended standards. The purpose of this study was to access the conditions of radiology units at Mazandaran University hospitals and compare them with the standards of ICRU NCRP and ICRP. Radiology unit is the most expensive section of any hospital for its instruments, manpower and space provided. In a study conducted in 51centers on radiology staff, radiography room and protective barrier, ray leakage, the outcome were 89%, 82%, 77% and 37% respectively. It was found that the condition of these centers regarding the protective barriers is very unsuitable due to unawareness of the leakage (5, 6).Considering the mentioned necessities, in this study, the condition of radiography centers affiliated to the Mazandaran University of Medical Sciences was studied for the type and the rate of problem, in order to provide a proper solving method. Results Data were collected through, observation, interviewing and filling questionnaire. Results show that, the situations of the radiology units are for from international standard, to such an extent that it is matched clout 50%. Conclusion The results showed that, none of the dark rooms are standard, and do not have proper alarm signal. In 63% of these units there no tiling system about staff protection from radiation. Defects in radiography room, protective barrier and lack looking rays were 60%, 51% and 47% respectively. Referring to the obtained data, periodic supervision, and obeying of the standards are necessary.
Keywords: Radiology center; Safety; Radiology standards; Staff; Mazandaran.